(2x+3)(8-4x)=0

Simple and best practice solution for (2x+3)(8-4x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3)(8-4x)=0 equation:



(2x+3)(8-4x)=0
We add all the numbers together, and all the variables
(2x+3)(-4x+8)=0
We multiply parentheses ..
(-8x^2+16x-12x+24)=0
We get rid of parentheses
-8x^2+16x-12x+24=0
We add all the numbers together, and all the variables
-8x^2+4x+24=0
a = -8; b = 4; c = +24;
Δ = b2-4ac
Δ = 42-4·(-8)·24
Δ = 784
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{784}=28$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(4)-28}{2*-8}=\frac{-32}{-16} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(4)+28}{2*-8}=\frac{24}{-16} =-1+1/2 $

See similar equations:

| x/2-x/3=x/4+1/2 | | 3+77x=44x+27 | | 10*p=40 | | x/5+3=2x+10 | | 4y+y´=0 | | 180=45-x+23-x-35 | | (D^2+4D+5)y=10 | | 3x+9/2x-7=0 | | -.4y-2(3-5y)+2=-3y-0.5(-3-2y) | | |2x-3|=3x-8 | | 3(x-7)+5=x-4 | | 18+6y=y+43 | | 3z/7+3=-5 | | 2/3x(4-5)=0 | | z/7+1=4 | | 5=2(x+7) | | 7x-18=3x+30 | | 3x-14=2x=9x | | 9+2x+5x(5-1)=36 | | 5x+3-x-2=41 | | 12x+9-10x+7=38 | | 6x-26+5x=18 | | 6r^2+12r-23=2 | | -2x-5x=4x-3-3x | | 2(4x+1)(x−1)+3=0 | | 5(5x-6)=-67. | | 2x-27=3x-20 | | -9y-14=4y+25 | | 6x+7=-8+2x+23 | | 3x+4x+5x=6x | | -133+13x=8x+97 | | 2y+7=-8-3y |

Equations solver categories